1 5/16 : (9 - 6 1/8 · 1 2/7) = 1 1/6
1) 6 1/8 · 1 2/7 = 49/8 · 9/7 = (7·9)/(8·1) = 63/8 = 7 7/8
2) 9 - 7 7/8 = 8 8/8 - 7 7/8 = 1 1/8
3) 1 5/16 : 1 1/8 = 21/16 : 9/8 = 21/16 · 8/9 = (7·1)/(2·3) = 7/6 = 1 1/6
ответ: 1 целая 1/6.
5/6
Пошаговое объяснение:
1) 6 1/8·12/7=7 7/8
2) 9- 7 7/8= 1 1/8
3) 15/16:1 1/8= 5/6
1 5/16 : (9 - 6 1/8 · 1 2/7) = 1 1/6
1) 6 1/8 · 1 2/7 = 49/8 · 9/7 = (7·9)/(8·1) = 63/8 = 7 7/8
2) 9 - 7 7/8 = 8 8/8 - 7 7/8 = 1 1/8
3) 1 5/16 : 1 1/8 = 21/16 : 9/8 = 21/16 · 8/9 = (7·1)/(2·3) = 7/6 = 1 1/6
ответ: 1 целая 1/6.
5/6
Пошаговое объяснение:
1) 6 1/8·12/7=7 7/8
2) 9- 7 7/8= 1 1/8
3) 15/16:1 1/8= 5/6